1993
DOI: 10.5035/nishiseisai.42.1056
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Intracompartmental Pressure, Berore, During and After Exercise.

Abstract: Chronic compartmentsyndrome is a cause of pain in the lower extremity, and is a common disability in athletes.The significance of intracompartmental pressure in the diagnosis of chronic compartment syndrome is controversial.We measured anterior intracompartmental pressure in five healthy men before, during, and after exercise, using the Millar catheter system.The exercise consisted of active dorsif lexion for 3 minutes and running on a treadmill for 5 minutes. The resultswere compared with those of a previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Contraction leading to fatigue of the biceps and triceps, increased the elastic coefficient in both flexion and extension movements of the elbow joint. Previous reports found that after exercise it took approximately 8 minutes for the intramuscular pressure to become constant owing to temporary muscle hardening caused by muscle activity 10) . This hardening is caused by an increase in local blood flow in muscles and water transfer between tissues 1,3) .…”
Section: Discussionmentioning
confidence: 99%
“…Contraction leading to fatigue of the biceps and triceps, increased the elastic coefficient in both flexion and extension movements of the elbow joint. Previous reports found that after exercise it took approximately 8 minutes for the intramuscular pressure to become constant owing to temporary muscle hardening caused by muscle activity 10) . This hardening is caused by an increase in local blood flow in muscles and water transfer between tissues 1,3) .…”
Section: Discussionmentioning
confidence: 99%